Examining features of radiation-induced damage to PADC observed using FT-IR analysis: Radiation tolerance of methine groups at three-way junctions. (September 2021) - Kusumoto, Tamon; Kanasaki, Masato; Ishikawa, Ippei; Barillon, Rémi; Honda, Yoshihide; Tojo, Sachiko; Kodaira, Satoshi; Yamauchi, Tomoya
Abstract: We report chemical damage to the methine (CH) and methylene (CH2 ) groups in poly(allyl diglycol carbonate) (PADC), which is a polymeric nuclear track detector, under gamma rays and heavy ions (C and Kr) using Fourier Transform Infrared (FT-IR) analysis. By comparing the IR spectrum of PADC from 2700 to 3100 cm −1 to that of diethyleneglycol bis allylcarbonate (ADC), which is a monomer of PADC, we found that the peak at 2920 cm −1 was assigned to the methine group at the three-way junction. The methine group was barely damaged by gamma rays and heavy ions. It is necessary that at least two tracks interact with a single PADC unit to damage the methine group. Highlights: The mechanism of damage to methine groups in PADC is investigated by FT-IR. Methine groups in PADC are barely affected even under irradiation from heavy ions. At least two tracks have to interact with a single PADC unit to damage the methine group.